Cross-cultural challenges faced by international students: A case study of Indian postgraduate students at a London-based business school - Astley, Marcus (Journal of International Students, 2024)
This case study was undertaken in a London-based business school and explores the cross-cultural challenges faced by students who have relocated from India to the UK for one-year postgraduate (PG) business master’s courses. Primary data were collected in two stages: semi-structured interviews, followed by a survey. The paper draws on the literature related to socio-cultural theory. It then reviews the findings of the research as to the cultural challenges the students have faced in the UK, whether in their studies, or their wider social lives. Finally, it integrates these findings into the extant literature and proposes a set of recommendations for consideration by the business school. Some of these may also have relevance for other Higher Education (HE) institutions working with Indian students.